Melatonin Ameliorates Coxsackievirus B3-Induced Myocarditis by Regulating Apoptosis and Autophagy - Sang, Yimiao; Gu, Xiaohong; Pan, Lulu; Zhang, Chunxiang; Rong, Xing; Wu, Tingting; Xia, Tianhe; Li, Yuechun; Ge, Lisha; Zhang, Yuanhai; Chu, Maoping (Frontiers in Pharmacology, 2018)
The current therapeutics of viral myocarditis is far from satisfactory. Recently, melatonin, a molecule produced by the pineal gland and other organs, has been found to have protective effects on ischemic heart injuries. However, the potential therapeutic effect of melatonin on viral myocarditis is currently unknown. In this study, the effect of melatonin on viral myocarditis as well as its potential mechanisms were determined in a mouse model of myocarditis was induced by coxsackievirus B3 infection. Mice with CVB3-induced myocarditis displayed inflammatory cell infiltrations and interstitial edemas. Melatonin treatment dramatically alleviated these myocardial injuries. In addition, the autophagy was adjusted, but apoptosis was inhibited in mouse hearts after treatment with melatonin. The results suggest that melatonin has a strong therapeutic effect on acute viral myocarditis, which is associated with changes of autophagy and apoptosis in heart. Melatonin might be a promising novel medication for viral myocarditis therapy.